Fresh Water Aquatic Training in Patients with Upright Posture Maintaining Disorders - Elena P. Ivanova; Andrey A. Lobanov; Sergey V. Andronov; Anatoliy D. Fesyun; Andrey P. Rachin; Gleb N. Barashkov; Elena N. Bogdanova; Irina A. Grishechkina; Andrey I. Popov; Olga D. Lebedeva; Maxim Yu. Yakovlev; Viktor V. Sidorov (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
The use of the fresh water aquatic training course, as a more gentle training method, may allow patients to ensure effective restoration of muscle functions responsible for maintaining an upright body position. A more accurate control of the course results can be performed using a virtual analysis carried out using the «Habilect» system that allows to determine the body parts attitude. Aim. To study the effect of training in fresh water using the Habilect system based on the Microsoft Kinect infrared sensor (video stabilometry) on motor functions that contribute to maintaining an upright body posture in patients with mild gait disturbances. Material and methods. An open descriptive study was conducted including 12 patients (7 men, 5 women), aged 40 to 62 years, with upright posture maintaining disorders, which correspond to the functional diagnosis encoded by the ICF «Gait Stereotype Functions» B770.1 - mild violations (5-24%). A group of subjects (n = 12), in addition to basic therapy and training with an exercise therapy instructor, underwent aquatic training in fresh water for two weeks (30 minutes, 6 days a week). Assessment methods: the research was carried out using the Habilect gait video analysis system before and after the rehabilitation course. The χ2 test was used to assess the significance of differences between groups of qualitative variables. When analyzing quantitative variables, the Shapiro-Wilk's (W) test was performed. For abnormal distribution, the data is in Me format [Q25-Q75]. The Wilcoxon T-test was used to assess the significance of differences in quantitative variables of the two studied groups. The processing of the obtained research results was carried out using the Statistica for Windows, v. 8.0 (StatSoft Inc., USA) and Microsoft Excel (Microsoft, USA). The significance of the differences was considered established at p <0.05. Result and discussion. When examining the amplitude of body deflection along the X-axis before training, they were 3.25 cm [-98 cm; 93.9 cm], after - -9.96 cm [-100.92 cm; -81.96 cm], on the Y-axis before training - -29.01 cm [-29.01 cm; 13.76 cm], after --30.59 cm [-30.59 cm; 31.09 cm], on the Z-axis before training - 388.1 cm [369.22 cm; 393.39 cm], after training - 380.96 cm [377.98cm, 400.05 cm], deviation of the body movement vector before training 16.45 cm [7.46 cm; 338.67 cm], after training - 324.7 cm [324.7 cm; 342.56 cm]. When examining the amplitude of head deflection along the X-axis before training, they were -0.92 cm [-1.24 cm; -0.92 cm], after - 1.5 cm [-10.19 cm; 2.38 cm], Y-axis before training - 125.33 cm [61.13 cm; 128.94 cm], after - 107.42 cm [52.49 cm; 107.42 cm], along the Z-axis before training - -8.59 cm [-8.97 cm; -5.33 cm], after training - -14.89 cm [-14.89 cm, -3.45cm]. When calculating the increase in deviation (deviations of the main body axes from the initial value) using the Wilcoxon T-test revealed statistically significant deviations in the X-axis (an increase of 306.5%, p = 0.0504), the Z-axis (an increase of 112.68%, p =0.0225) and the Body Angle parameter (an increase of 1973.86% p = 0.0323). When calculating the increase in the deviation of the head axes from the initial value using the Wilcoxon T-test, statistically significant deviations were revealed along the X axis (increase of 163.04%, p = 0.0280), the Y axis (increase of 85.71%, p = 0.0199) and the parameter Z (an increase of 173.34% p = 0.0292). The study revealed a decrease in the body axes deviations amplitude in all 3 planes, which indicates an improvement in the work of all brain parts that are responsible for the coordination of motor functions and their vegetative support, an improvement in functional interaction within individual muscle chains. The reduction in the head and neck muscles in compensatory balancing participation during walking and maintaining a vertical body posture mainly due to the muscles of the lower extremities and pelvis contributes to the prevention of arterial and venous circulation disorders in the head and neck and makes training not only more effective, but also safer. Conclusion. Due to the decrease in the amplitude of deviations along all three axes (Z, Y, X), the course of aquatic training contributes to the correction of upright posture maintaining disorders, a statistically significant decrease in the amplitude of head and neck movements.